Analysis of simulation approaches for the breakdown characteristics of SOI high-voltage PMOS in a fixed power supply. (February 2015) - Qiao, Ming; Dai, Gang; He, YiTao; Wu, WenJie; Zhang, Bo; Li, ZhaoJi
Highlights: A simulation approach for breakdown characteristics of SOI HV PMOS is proposed. A SOI VLD field PMOS is investigated in a fixed power supply. The proposed simulation approach reflects more realistic device characteristics. The effect of REBULF is revealed for SOI HV PMOS in a fixed HV power supply. Abstract: A novel simulation approach for the breakdown characteristics of SOI high-voltage (HV) PMOS in a fixed power supply application is proposed. The different optimized parameters for the SOI HV PMOS can be achieved by the conventional and proposed simulation approaches. A SOI variation of lateral doping (VLD) field PMOS, which is widely used in the level-shift circuit is investigated by the conventional and novel simulation approaches. For the level-shift circuit with power supply of 400 V, the breakdown voltage (BV) of the optimized SOI VLD field PMOS increases from 520 V with the conventional simulation approach to 646 V with the proposed simulation approach. Moreover, the corresponding optimized doping concentration of p-drift region with the proposed approach is higher than that with the conventional approach, thus greatly reducing the specific on-resistance ( R on, sp ). The SOI VLD field PMOS actually has a more robust breakdown voltage and lower R on, sp in the fixed power supply. The BV and R on, sp of SOI HV PMOS can be truly reflected and the effect of reduced bulk field (REBULF) is revealed in the fixed HV power supply by employing the novel simulation approach.